Elucidating the metabolic pathways responsible for higher alcohol production in Saccharomyces cerevisiae - Styger, Gustav (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Wine Biotechnology))--University of Stellenbosch, 2011.